Addressing depression in older adults with Alzheimer’s through cognitive behavioral therapy: systematic review and meta-analysis - González-Martín, Ana María; Aibar Almazán, Agustín; Rivas Campo, Yulieth; Rodríguez Sobrino, Noelia; Castellote Caballero, Yolanda (Frontiers in Aging Neuroscience, 2023)
Objectives This systematic review and meta-analysis was conducted to provide an analysis of the published data about the effects of cognitive behavioral therapies on the depression of older adults with a diagnosis of Alzheimer’s disease. Methods This study was performed following the PRISMA 2020 guidelines. The search was performed between March and April 2023, using four electronic databases: PubMed, Web of Science, Cinhal and Scopus. Different keywords combined with Boolean operators were utilized. Only 11 articles were included out of the initial 212. Results Cognitive behavioral therapy was found to reduce depression in individuals with Alzheimer’s, including treatments with low frequency but a longer intervention time. Conclusion This systematic review and meta-analysis found that the psychosocial therapy cognitive behavioral therapy is effective in improving depression in individuals with a diagnosis of Alzheimer’s. However, results are inconclusive due to the disparity of the findings and the heterogeneity of the applied protocols, so more studies are needed on this topic. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=416396, CRD42023416396.